2017
DOI: 10.3390/plants6030040
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and Nitrate Differentially Modulate the Symbiotic Performances of Healthy and Virus-Infected Bradyrhizobium-nodulated Cowpea (Vigna unguiculata), Yardlong Bean (V. unguiculata subsp. sesquipedalis) and Mung Bean (V. radiata)

Abstract: The effects of 2 mM silicon (Si) and 10 mM KNO3 (N)—prime signals for plant resistance to pathogens—were analyzed in healthy and Cowpea chlorotic mottle virus (CCMV) or Cowpea mild mottle virus (CMMV)-infected Bradyrhizobium-nodulated cowpea, yardlong bean and mung bean plants. In healthy plants of the three Vigna taxa, nodulation and growth were promoted in the order of Si + N > N > Si > controls. In the case of healthy cowpea and yardlong bean, the addition of Si and N decreased ureide and α-amino acids (AA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Other studies addressing the impacts of silicon on legumes (listed in Table 2) also report how silicon supplementation increased nodule dry biomass in two different cultivars of soybean (Steiner, Zuffo, Bush, & Santos, 2018) and in three different Vigna plants (Izaguirre‐Mayoral, Brito, Baral, & Garrido, 2017). In addition, Kurdali, Al‐Chammaa, and Al‐Ain (2018) showed that the effects of silicon on root nodulation and nitrogen fixation were more profound under salinity and/or water stress in Sesbania legume but relatively minor in the absence of such stress.…”
Section: Evidence For Silicon Affecting Legumesmentioning
confidence: 99%
“…Other studies addressing the impacts of silicon on legumes (listed in Table 2) also report how silicon supplementation increased nodule dry biomass in two different cultivars of soybean (Steiner, Zuffo, Bush, & Santos, 2018) and in three different Vigna plants (Izaguirre‐Mayoral, Brito, Baral, & Garrido, 2017). In addition, Kurdali, Al‐Chammaa, and Al‐Ain (2018) showed that the effects of silicon on root nodulation and nitrogen fixation were more profound under salinity and/or water stress in Sesbania legume but relatively minor in the absence of such stress.…”
Section: Evidence For Silicon Affecting Legumesmentioning
confidence: 99%
“…Studies have confirmed that silicon fertilizer is beneficial for plant growth and development and can enhance plant biomass and yield. For example, silicon fertilizer can improve photosynthesis [9,10], increase crop yield by enhancing gas exchange properties and the chlorophyll content in leaves to reduce oxidative damage [11,12], improve root colonization [13], and promote the growth and symbiosis of beneficial microorganisms [14]. Moreover, silicon fertilizer can reduce the harm of insects and pathogens [15]; improve the nutrient utilization efficiency of P, Ca, K, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Si supplementation frequently increases nodule abundance, nitrogenase activity (indicative of increased N-fixation) and concentrations of nitrogenous compounds (protein and amino acids) in Medicago spp. and other legumes (Nelwamondo & Dakora 1999;Izaguirre-Mayoral et al 2017;Putra et al 2022), especially when plants are under stress (e.g. Al Murad & Muneer 2022).…”
Section: Introductionmentioning
confidence: 99%